Use and Perceptions of Electronic Cigarettes among Young Chinese Generation: Expanding the Theory of Planned Behaviour - Wang, Lei; Zhang, Qi; Cao, Meng-Ru; Weng Wong, Philip Pong (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The Theory of Planned Behaviour (TPB) is recognized as powerful predictive model to explain consumer purchase behaviour. However, there have been relatively few studies that determine the role of TPB’s constructs in e-cigarettes decision-making process. Moreover, the TPB ignores the impulsive motivation (i.e., hedonism) and unconscious motivation (i.e., habit) and perceived knowledge in the literature. This study adopted a quantitative method based on a survey with 293 young respondents using e-cigarettes. The proposed hypotheses were empirically tested with SPPS and AMOS. This study revealed that perceived knowledge positively influenced attitude, subjective norm (SN), and perceived behavioural control (PBC) respectively. The results showed a positive relationship between attitude, SN, PBC and intention, and intention positively influenced actual e-cigarettes use behaviour. The results also demonstrated how consumers’ hedonic motivation and habit influence intention. Lastly, the theoretical and practical implications and limitations were discussed.